Internet Addiction in Preuniversity Students in East Malaysia: Prevalence and its Association with Stress and Depre - Whye Lian, Cheah; Myat, Su Bo; Lai Hui, Yee; Atiqah Safawati, Idris; Brianna Jaswinta, Bia; Kimberly Claire, Deser; Han Yong, Lim (Wolters Kluwer - Medknow, 2022)
Objective: This study examined the differences between internet addiction, problematic Internet use, and pathological Internet use and their association with stress and depression among pre-university students in a public university in East Malaysia. Methods: It was a cross‑sectional study using the self‑administered questionnaire that consists of socio-demographic information, the Internet addiction test (IAT), patient health questionnaire (symptoms of depression), and Perceived Stress Scale‑10. Data were analyzed using the IBM SPSS software version 23. Results: Two hundred and sixty‑six respondents participated in the study (response rate of 95.7%). About 12% of the respondents reported having a high level of perceived stress and 69.9% with moderately severe and severe depression. For the Internet addiction profile, 21.4% reported being problematic Internet users and 21.4% were pathological Internet users. Multinomial logistics regression analysis showed no significant effect from gender, perceived stress, and depression on problematic Internet addiction. On the outcome of pathological Internet addiction compared to non-internet addiction (reference category), male has higher pathological Internet addiction as compared to female (odd ratio = 2.78); those who have moderately severe‑to‑severe depression are more likely to be pathological Internet addiction as compared to non-internet addiction (1/0.325 = 3.07). Conclusion: The study revealed that problematic and pathological Internet use is prevalent in our sample, and pathological Internet addiction was associated with the symptom of depression and gender. Early intervention and detection of problematic internet use may prevent the development of maladaptive coping responses that lead to Internet addictive use.